Impact of Digital Technologies on Novel Endpoint Capture in Clinical Trials. Issue 6 (13th October 2017) - Clay, Ieuan
Abstract : Digital technologies have been successfully deployed in clinical settings for many years, yet recent advances in hardware and analytic capabilities have driven an explosion in interest over the potential of digital medicine to change how drugs are developed, centering on how we interact with patients, treat patients, and capture information about patients.